Penyuluhan Peraturan Berlalu-Lintas kepada Angkutan Online di Kota Bandar Lampung - Karami, Muhammad; Herianto, Dwi; Iswan; Junaidi, Tas'an (Nemui Nyimah, 2024)
The aim of this community service activity is to increase the understanding of online transport drivers in Bandar Lampung City about traffic accidents, the causes of traffic accidents and traffic safety on the highway. It is hoped that this activity can bring more safety on the road with or respect other road users so that it can increase safety on the road, improve the performance of the road-traffic system. This service activity will be carried out in Bandar Lampung City. The target community for this service program are online transportation service drivers in the city of Bandar Lampung. The service method is in the form of community participation with indicators of community participation in activities through outreach activities. The stages of this activity start with gathering drivers for online transportation services in Bandar Lampung City. The lecture activity involves showing traffic regulations using a screen and LCD projector to display the contents of the lecture, then continued with question and answer activities.